EKOSISTEM MANGROVE DALAM MITIGASI GELOMBANG BESAR DI TELUK SEREWE LOMBOK TIMUR - Irwansah, Irwansah; Mahariyanti, Ermila (LPPM Institut Pendidikan Nusantara Global, 2021)
Serewe Bay is one of the bays in the Lombok area, West Nusa Tenggara which is vulnerable to natural disasters including the Big Wave. For this reason, the researcher aims to determine the types of plants that play a role in mitigating big waves and the density level of the mangrove ecosystem in Serewe Bay. This research was conducted using the Belt Transect method, namely in Serewe Bay. Mangrove plant data were obtained by making plots at each research location. In each plot, 3 plots were made, namely 10 x 10 m (for trees), 5 x 5 m (saplings), and 2 x 2 m (for seedlings). Mangroves in Serewe Bay found 6 species that have the potential to mitigate big waves, namely Sonneracia alba with a relative density of seedlings (14.64%), Saplings (29.12%), Trees (73.33%). Dolichandrone spathacea relative density of seedlings (10.18%), Saplings (15.06%) Trees (12.33%). Rhizopora mucronata with a relative density of seedlings (10.14%), Saplings (20.65%), Trees (10.33%). Avicennia ofiicinalis relative density of seedlings (6.90%), Saplings (31.14%), Trees (9.33%). Casuarina equisetifolia relative density of seedlings (5.58%), Saplings (20.10%), Trees (8.33%). Hibiscus tillaceus relative density of seedlings (4.45%), Saplings (14.10%), Trees (5.67%).